Genome analysis of a halophilic Virgibacillus halodenitrificans ASH15 revealed salt adaptation, plant growth promotion, and isoprenoid biosynthetic machinery - Sharma, Anjney; Singh, Ram Nageena; Song, Xiu-Peng; Singh, Rajesh Kumar; Guo, Dao-Jun; Singh, Pratiksha; Verma, Krishan K.; Li, Yang-Rui (Frontiers in Microbiology, 2023)
Globally due to widespread dispersion, intraspecific diversity and crucial ecological component of halophilic ecosystems, Virgibacillus is considered as one of the key models for ecological, adaptative and biotechnological applications research in saline environments. With this aim, the present study was to enlighten the plant growth promoting features and investigate the systematic genome of a halophilic bacteria Virgibacillus halodenitrificans ASH15 through single‐molecule real‐time (SMRT) sequencing technology. Results showed that strain ASH15 could survive in high salinity up to 25% (w/v) NaCl concentration and express plant growth promoting traits such as nitrogen fixation, plant growth hormones, hydrolytic enzymes, which sustain in salt stress. The Results of pot experiment revealed that strain ASH15 significantly enhanced the sugarcane plant growth (root shoot length and weight) under salt stress condition. Moreover, the sequencing analysis of strain ASH15 genome exhibited that this strain contained a circular chromosome of 3,832,903 bp with an average G+C content of 37.54%. There were around 3721 predicted protein‐coding sequences (CDSs), 24 rRNA genes, and 62 tRNA genes. Genome analysis revealing that the genes (CDS) related to synthesis and transport of compatible solutes (glycine, betaine, ectoine, hydroxyectoine, glutamate) confirm the salt stress as well as heavy metal resistance. Furthermore, functional annotation showed that the strain ASH15 encode genes for root colonization, biofilm formation, phytohormone IAA production, nitrogen fixation, phosphate metabolism and siderophore production, which are beneficial for plant growth promotion. Strain ASH15 also has genes resistance response towards antibiotics and pathogens. In addition, analysis also revealed that genome strain ASH15 has insertion sequences and CRISPRs which suggest its ability to acquire new genes with horizontal gene transfer and immunity to the attack of viruses. This work provides the knowledge of the mechanism through which V. halodenitrificans ASH15 tolerates salt stress. During Genome analysis it was found that strain ASH15 has MVA pathway to synthesize isoprenoids more precisely “Squalene”. Squalene has various applications such as an antioxidant, anti-cancer agent, anti-aging, hemopreventive, anti-bacterial, adjuvant for vaccines and drug carrier, and detoxifier. Therefore, our findings indicated that strain ASH15 has enormous potential in industries such as pharmaceuticals, cosmetic, and food along with agriculture.